The application of photogrammetric orthomosaics for documentation of palaeontological sites - Díaz Martínez, Ignacio (2018)
Fil: Díaz Martínez, Ignacio. Universidad Nacional de Rio Negro. Instituto de Investigaciones en Paleobiologia y Geologia. Río Negro, Argentina.